Slim Thabet, L'économie politique du capitalisme raisonnable. Essai sur les fondements institutionnalistes de la pensée économique de John Maynard Keynes - Slim Thabet (Revue de la Régulation)
In the second volume of the monumental biography R. Skidelsky established on J. M. Keynes, we can find an enigmatic, if not strange, passage. According to R. Skidelsky, J. R. Commons was “an important, if unacknowledged influence on Keynes”. This feeling of strangeness is even stressed by the remarks expressed by J. M. Keynes himself in a letter that remained to J. R. Commons.In that letter indeed, dated from the 26th April 1927, Keynes was writing, “there seems to me to be no other economist with whose general way of thinking I feel myself in such a genuine accord”. R. Skidelsky’s passage, as well as J. M. Keynes’ epistolary sentiments, raise a lot of questions to which this thesis is attempting to answer: First of all, when, and how did the relationship between J. M. Keynes and J. R. Commons begin? Then, if there actually was an influence by J. R. Commons on J. M. Keynes, at which level must it be situated? Eventually, insomuch as J. R. Commons represents one of the central figures of the American Historical Institutionalism and beyond the relationship between J. R. Commons and J. M. Keynes, can one consider that not only the institutions play a fundamental role in J. M. Keynes’ economic thought, but also that his conception of institutions is itself peculiar?In order to answer these questions, one must now seriously reconsider the evolution of J. M. Keynes’s economic thought in the light of J. R. Commons influence. We suggest to call this influence “the Commons Hypothesis”. Accordingly, J.M. Keynes’ economic thought is revisited through the concept of collective action as one among the incontrovertible ways of the resolution of modern capitalism “Economic Problem” that leads to a Reasonable capitalism. That way, which acknowledges the dynamics of conflicts and compromises, necessarily goes through the institutions as entities of mediation both between the micro and macroeconomic levels and between the groups of economic agents and the State.